2021
DOI: 10.3389/fendo.2021.744868
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor in Diabetic Foot Ulcer: Progress and Therapeutic Prospects

Abstract: Diabetic foot ulcer (DFU) is a combination of neuropathy and various degrees of peripheral vasculopathy in diabetic patients resulting in lower extremity infection, ulcer formation, and deep-tissue necrosis. The difficulty of wound healing in diabetic patients is caused by a high glucose environment and various biological factors in the patient. The patients’ skin local microenvironment changes and immune chemotactic response dysfunction. Wounds are easy to be damaged and ulcerated repeatedly, but difficult to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 126 publications
0
59
0
1
Order By: Relevance
“…Neo-vascularisation at the wound bed is essential for skin regeneration and healing in diabetic wounds [ 38 ]. Earlier studies have reported the requirement of additional application of angiogenic growth factors such as FGF (fibroblast growth factor) and VEGF (vascular endothelial growth factor) to induce neovascularisation in diabetic wounds [ 39 , 40 ]. In this study, it was observed that the Tylotoin-MP, LLKKK-18-NP and NF-NP-MP treatments promoted greater neo-vascularisation ability when compared to the Control and NF alone treatment suggesting the growth factor upregulation and blood vessel formation ability of the bioactive peptides applied to the wound bed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Neo-vascularisation at the wound bed is essential for skin regeneration and healing in diabetic wounds [ 38 ]. Earlier studies have reported the requirement of additional application of angiogenic growth factors such as FGF (fibroblast growth factor) and VEGF (vascular endothelial growth factor) to induce neovascularisation in diabetic wounds [ 39 , 40 ]. In this study, it was observed that the Tylotoin-MP, LLKKK-18-NP and NF-NP-MP treatments promoted greater neo-vascularisation ability when compared to the Control and NF alone treatment suggesting the growth factor upregulation and blood vessel formation ability of the bioactive peptides applied to the wound bed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…China and Japan have focused on utilizing the potential of FGF for wound healing, particularly in the case of surgical wounds, including skin grafts, obstetric wounds, and surgical incisions, and for the treatment of burns and ulcers [174][175][176]. FGF1, FGF2, FGF4, FGF7, FGF16, FGF21, and FGF23 have been found to have good therapeutic outcomes for diabetic foot ulcers [177]. From the literature reviewed above, it seems that FGF can serve as a very promising therapy for tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the pathological changes at different stages in diabetic chronic wounds, the emergence of multiple drug-resistant bacteria, and the effects of some other treatments and drugs on wound healing. 76 , 77 …”
Section: Deficiencies Of Existing Materials and Properties Of Ideal W...mentioning
confidence: 99%